We know that y1(x) for z = (-00,00). = e-3x is a solution to the differential equation D²y - 12Dy – 45y = 0 for x = (-∞, ∞). Use the method of reduction of order to find the second solution to D²y - 12Dy - 45y = 0 (a) After you reduce the second order equation by making the substitution w = u', you get a first order equation of the form w' f(x, w) = Note: Make sure you use a lower case w, (and don't use w(t), it confuses the computer). (b) A second solution to D²y - 12Dy - 45y = 0 for x = (-∞, ∞) is Y2(x) = =
We know that y1(x) for z = (-00,00). = e-3x is a solution to the differential equation D²y - 12Dy – 45y = 0 for x = (-∞, ∞). Use the method of reduction of order to find the second solution to D²y - 12Dy - 45y = 0 (a) After you reduce the second order equation by making the substitution w = u', you get a first order equation of the form w' f(x, w) = Note: Make sure you use a lower case w, (and don't use w(t), it confuses the computer). (b) A second solution to D²y - 12Dy - 45y = 0 for x = (-∞, ∞) is Y2(x) = =
Algebra & Trigonometry with Analytic Geometry
13th Edition
ISBN:9781133382119
Author:Swokowski
Publisher:Swokowski
Chapter5: Inverse, Exponential, And Logarithmic Functions
Section: Chapter Questions
Problem 18T
Related questions
Question
![We know that y1(x)
for z = (-00,00).
= e-3x
is a solution to the differential equation D²y - 12Dy – 45y = 0 for x = (-∞, ∞). Use the method of reduction of order to find the second solution to D²y - 12Dy - 45y = 0
(a) After you reduce the second order equation by making the substitution w = u', you get a first order equation of the form
w'
f(x, w) =
Note: Make sure you use a lower case w, (and don't use w(t), it confuses the computer).
(b) A second solution to D²y - 12Dy - 45y = 0 for x = (-∞, ∞) is
Y2(x) =
=](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2F9003f062-53c9-4ed8-afe3-2b10c28538b9%2Fae2e901a-8b7e-4fde-a062-ca389a930323%2Fcskfxr_processed.png&w=3840&q=75)
Transcribed Image Text:We know that y1(x)
for z = (-00,00).
= e-3x
is a solution to the differential equation D²y - 12Dy – 45y = 0 for x = (-∞, ∞). Use the method of reduction of order to find the second solution to D²y - 12Dy - 45y = 0
(a) After you reduce the second order equation by making the substitution w = u', you get a first order equation of the form
w'
f(x, w) =
Note: Make sure you use a lower case w, (and don't use w(t), it confuses the computer).
(b) A second solution to D²y - 12Dy - 45y = 0 for x = (-∞, ∞) is
Y2(x) =
=
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 2 steps with 3 images
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)
Recommended textbooks for you
Algebra & Trigonometry with Analytic Geometry
Algebra
ISBN:
9781133382119
Author:
Swokowski
Publisher:
Cengage
Algebra & Trigonometry with Analytic Geometry
Algebra
ISBN:
9781133382119
Author:
Swokowski
Publisher:
Cengage